(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Multi-modality image-guided core needle biopsy (ultrasound, computed tomography and magnetic resonance imaging) has become a mainstay in paediatric oncology to avoid invasive and time-consuming surgery while simultaneously improving the diagnostic accuracy and reducing the incidence of sequelae. But a tiny targeted piece has the same quantity and quality of abnormal parts as surgery does. Objective: To evaluate the diagnostic reliability of image-guided core biopsy in soft tissue or bone tumours in paediatric patients. Methods: This retrospective study included patients who had clinical and radiological examinations due to solid masses that were considered neoplastic or who were under follow-up oncology treatment with suspected metastasis. All patients underwent image-guided Tru-cut biopsies to confirm or rule out the diagnosis of tumour. The study began in September 2020 and will go until September 2025. Results: The total number of patients included in the study was one hundred. Sixty-five were men and 35 were females, with a mean age of 1.9±2.4 years. The first trial in 90% of patients provided a sufficient tissue sample; the second trial was used for 10% of patients to collect enough tissue. A Tru-cut needle biopsy was the method of choice in 95 (95%) patients in both trials, whereas in 5 (5%) patients an open biopsy was performed. Of the patients diagnosed using tru-cut needle biopsies, forty (40%) were diagnosed with non-Hodgkin’s lymphoma, thirty (30%) with neuroblastoma, ten (10%) with osteosarcoma, ten (10%) with rhabdomyosarcoma, three (3%) with nephroblastoma and two (2%) had boney metastases. 95% of patients were appropriately diagnosed with a tru-cut needle biopsy. Conclusion: image-guided percutaneous tru-cut needle biopsy allows for accurate and safe sampling of solid tumours in children. It can yield a reliable diagnosis in cases of solid abdominal tumours in children.